Impacts of planting spacing and nitrogen level on growth, yield and quality of baby corn and green fodder from the same crop (Journal of the Bangladesh Agricultural University, 2020)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to investigate the effect of planting spacing and nitrogen levels on yield and quality of baby corn and green fodder. The experiment comprised three plant spacing viz. 45 cm × 30 cm, 45 cm × 20 cm, 45 cm × 10 cm and five nitrogen levels viz. 0, 80, 120, 160 and 200 kg N ha-1. The experiment was laid out in a randomized complete block (RCB) design with three replications. The highest number of leaves plant-1, total dry matter plant-1 at 30 DAS, chlorophyll content at 65 DAS were observed by at 45 cm × 20 cm spacing fertilized with 200 kg N ha-1. The highest number of cobs plant-1 and cob length without husk were recorded in 45 cm × 30 cm which was at par with 45 cm × 20 cm. The highest cob length with husk, cob diameter with husk, cob diameter without husk, cob yield with husk, cob yield without husk, fodder yield and protein content of cob were found at 45 cm × 20 cm spacing while the lowest values were recorded at 45 cm × 10 cm spacing. The highest number of cobs plant-1, cob length with husk, cob length without husk, cob diameter with husk, cob yield with husk, cob yield without husk, fodder yield and protein content of cob were observed by at 45 cm × 20 cm spacing fertilized with 200 kg N ha-1. Therefore, it may be concluded that planting of baby corn at 45 cm × 20 cm spacing along with application of 200 kg N ha-1 could be considered for obtaining higher cob yield, cob protein content (%) and green fodder from the same plant.J Bangladesh Agril Univ 18(1): 55–60, 2020https://doi.org/10.5455/JBAU.81179